Theoretical and practical aspects of the using surfactants in the technology of hot sweet dishes - Bloshchinska (Dudkina), Olena; Havrysh, Andrey; Ishchenko, Tatiana; Niemirich, Oleksandra; Tkachuk, Yuriy (My University, 2016)
Theoretical and practical study of the effect of surfactant on the quality of fondants special purpose. Проведено теоретичні та практичні дослідження впливу поверхнево активної речовини на якість фонданів спеціального призначення.
Keywords: surfactants; поверхнево-активні речовини; гарячі солодкі страви; hot sweet dishes; фондан; fondant; целіакія; celiac disease; кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи